Development of the methods of calculation of the electrical installations working operation in case of quality supply disturbance - Saeed, Ismael Kareem; younis, Kamal Sheikh (Sulaimani Journal for Engineering Sciences, 2020)
This paper proposes a method of calculating of asymmetrical modes of operation of electrical installations where simple and adequate loads equivalent circuits are available with working electrical equipment. So the mathematical model of equation system is derived as universal way for calculating the systems operating modes when it is subjected to a disturbance due to asymmetry. With the help of the obtained model we can calculate different cases of symmetry disturbances, all types of short circuits, between phase short circuits, any type of longitudinal asymmetry, open circuits when there is a resistance for the fault current at the place of damage In the given method, specific types of asymmetry are considered as particular cases and easily calculated from the generalized formula, which is essentially reduces the calculation and allows us to consider cases of asymmetry of any complexity. Therefore this method is offered as a basic for calculation of asymmetry when the system is subjected to a disturbance.
Keywords: Power systems; symmetrical components; asymmetry of supply; mathematical models